A high-performance regenerated graphite extracted from discarded lithium-ion batteries. (5th January 2021) - Ruan, Dingshan; Wang, Fengmei; Wu, Lin; Du, Ke; Zhang, Zhenhua; Zou, Ke; Wu, Xiaofeng; Hu, Guorong
Abstract : Lithium-ion batteries based on G-A-T-SGT@C anode display high specific capacity, excellent rate capability and outstanding cycling performance. Abstract : A feasible, environment-friendly and economical method to regenerate a graphite anode from discarded lithium-ion batteries is carried out. The regenerated graphite (G-A-T-SGT@C) was obtained after the treatment of scrapped graphite (SGT) via pyrolyzation, acid leaching, graphitization and coating by amorphous carbon. As a result, G-A-T-SGT@C has negligible impurities, smaller specific surface area, reduced pore defects and much higher degree of graphitization compared with SGT, which will enhance the electrochemical performance of G-A-T-SGT@C. Consequently, lithium-ion batteries with the G-A-T-SGT@C anode exhibited a high initial coulombic efficiency of 90.64%, a high specific capacity of 344 mA h g −1 at 0.2C, excellent rate capability and eximious cycling performance for more than 250 cycles at 0.5C, which is also outstanding compared with the performance of lithium-ion batteries using commercial graphite as the anode.